1923 Conn. Pub. Acts 3667 - (:unkn) unknown (My University, 1923)
Ch. 222, § 67: Restricted the use of rifle ranges affiliated with the NRA on Sundays to the hours of one and six in the afternoon.
Keywords: SHOOTING RANGES OR GALLERIES